Investigating the effectiveness of combining high-frequency chest wall oscillation with bilevel positive airway pressure in pneumonia patients: a retrospective cohort study - Ta-Wei Chao; Ya-Chen Kao; Hui-Ling Liu; Sheng-Hsiang Lin; Chin-Wei Kuo (BMC Pulmonary Medicine)
Abstract Background Pneumonia represents a significant global health burden with high morbidity and mortality rates, despite advances in therapeutic and preventive strategies. Airway clearance techniques (ACT), including High-Frequency Chest Wall Oscillation (HFCWO) and bilevel positive airway pressure (BiPAP), are critical in managing respiratory conditions. However, the combined effectiveness of BiPAP and HFCWO in treating adult pneumonia remains underexplored. Methods A retrospective cohort study was conducted at a college hospital in southern Taiwan, enrolling patients aged ≥ 18 years, admitted for pneumonia from January 2020 to December 2022, who received HFCWO therapy for ≥ 5 days in the ordinary ward. Exclusion criteria included prior mechanical ventilation before HFCWO initiation. Univariate and multivariable logistic regression models were used to assess the effectiveness of the combined use of BiPAP and HFCWO. Results A total of 271 patients received HFCWO and were enrolled for analysis, including 163 patients who received both BiPAP and HFCWO. Patients receiving both BiPAP and HFCWO were associated with decreased frequency of sputum suction (OR: 2.91, 95% CI: 1.46–5.78, P = 0.002), and reduced oxygen need post-HFCWO (OR: 0.55, 95% CI: 0.33–0.91, P = 0.021). However, there was no difference in hospital stay, respiratory failure, ICU admission, or hospital death between the groups. Additionally, there was no difference in these outcomes for patients who received HFCWO twice daily compared to those who received it once daily. Conclusions Combining BiPAP and HFCWO reduces the need for sputum suction and improves oxygen demand for patients but does not change hospital days, respiratory failure, or mortality. Further large prospective cohort studies are necessary to confirm the efficacy of this management approach.